Culture, gender and coffee drinking in Kuwait - Allafi, Ahmad R; Saleh, Asma; Aldughpassi, Ahmed; Al-Haifi, Ahmad R; Hersi, Abir; Ahmad, Farhia; Aljluwi, Sara (Progress in Nutrition, 2020)
The objective of the present study was to determine the effect of culture and gender on coffee drinking in Kuwait City, Kuwait. A cross-sectional study was conducted to achieve the objective of the study utilizing an online multiple-choice questionnaire. A total of 1483 participants aged between 18 and 35 years completed the online questionnaire. The largest portion of respondents were within the ages of 18-22 category (93.66 %, n=944), with 351 males (23.7%), and 1132 females (76.3%). 28.8% of males and 31% of females participants visit coffee shops 1-4 times a month, followed by 1-6 times a week (27.6% males, 23.2% females). The most consumed type of coffee among participants was Americano. Participants chose Starbucks as their favorite coffee shops (n=763, 51.4%). 66.7% (n=989) of participants do not check the products’ nutritional facts before purchasing. In terms of gender differences, females consume more coffee and have more calorie knowledge compared to males.